Systematic Review And Analysis Of Risk Management In Port Construction Projects - Afrina Khairunnisa (Journal of Industrial and Engineering System, 2021)
In construction projects, there will be no good risks or any risks. In this potential risk will cause problems, the smaller the potential risk faced, the smaller the problem and a large increase in the construction project from the budget and implementation of development. Moreover, the greater the risk, the bigger the problem and the smaller the profit, if not handled properly, it will hinder the development. Based on this research, the risks taken are in several categories, the most important risk is the technical project of 14 journals, then the second place is the technical internal risk of 7 journals. In this study, several journals were analyzed based on the category of Indonesia and China, with 3 journals and the second in Greece with 2 journals. Journals based on an analysis of the category of object themes in industry are 48%, then second in academics are 24%.